EFEKTIVITAS MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Jahring Jahring; Marniati Marniati (Universitas Muhammadiyah Semarang, 2020)
This research aims to determine the effectiveness of learning model inside outside circle on mathematics learning outcomes of students of grade IX SMP Negeri 3 Watubangga. This research is a research experiment (quasi experimental design) with the design of non-equivalent control group design. The population is all students of grade IX SMP Negeri 3 Watubangga as much as 52 people. Sampling with a totally sampling technique obtained the IXA class as the experimental class and the IXB class as the control class. The hypothesis test indicates that at the level of the significance α = 0.05, the value of tcount = 2,048 > ttable = 1,676. That means that H0 rejected and H1 accepted. So that the inside outside circle learning model is more effective to mathematics learning outcomes of students in grade IX SMP Negeri 3 Watubangga compared with conventional learning.